Motocykl–widmo, czyli meandry współczesnej fantastyki (Oleg Diwow, Рыжий пес иж) - Zywert, Aleksandra (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present paper aims at analyzing one of the most recent Divov’s stories entitled Рыжий пес Иж (2016). The text is interesting both due to its literary genre hybridity (it embraces elements of a melodrama, a horror story, a detective story, urban fantasy and a fairy tale) and the topics it touches upon (especially animalistic issues). Divov deploys the well-known literary and cinematic motif of a soul penetrating an object and creates a story of motorcycle haunted by a dog’s soul. Due to its original solutions (inter alia referring to films) Divov’s story is an interesting work illustrating the permanent interrelations between literatures and movies as well as the author’s exploration within this scope. Moreover, the manner of creating the animal character and placing it within the structure allow for including Divov’s story into the group of contemporary literary works reflecting the proanimal trends in Russian culture.